"So We Have to Teach Them or What?": Introducing Preservice Teachers to the Figured Worlds of Urban Youth through Digital Conversation. Issue 3 (March 2015) - Seglem, Robyn; Garcia, Antero
Background: Extant literature contends that it can be difficult for White preservice teachers to develop culturally relevant curriculum for the diverse students whom they will encounter in classrooms. Though there is a significant body of research about culturally responsive pedagogy, teacher education programs have struggled with how to best reconcile the needs of students of color with the experiences and misconceptions of White teachers. Purpose/Focus of Study: Using a figured world framework, we explore how social interaction made possible through digital tools shaped the actions and identities of 16 preservice teachers. Research Design: This qualitative case study focuses on three preservice teachers from Illinois to illustrate the cumulative and different process of change that each went through during his or her interactions with 10th-grade students from Los Angeles. Beginning with a holistic coding of the corpus of data, we looked at chat room transcripts, preservice teacher reflections, and writing samples from approximately 3 months of interaction between the two groups for this study. Coding the data in multiple cycles, we explored how preservice teachers' digital interactions with urban high school students contributed to preservice teachers' figured worlds. Findings: Providing preservice teachers with virtual access to urban youth's figured worlds allowed these future teachers to better understand the cultural artifacts of these students' worlds. In doing so, they were forced to acknowledge the importance of maintaining the belief that all students, including those from urban backgrounds, can and want to engage in rigorous learning. The project also provided the preservice teachers with an opportunity to learn more about the discourse of these students, giving preservice teachers insights about how to navigate the language of their students' cultures, to evaluate their students' academic language needs, and to instruct their students about shifting their language use to communicate across settings and purposes. Finally, opportunities to interact with urban youth allow preservice teachers to begin to develop identities that are more culturally responsive in nature. Conclusions: The results we explore in this article highlight the potential that virtual spaces offer for developing constructive dialogue between urban youth and preservice teachers, which can lead to reflective, culturally relevant teachers. "So we have to teach them or what? Well, they need to understand where we come from. We don't come from Illinois."